The role of amino bisphosphonates zoledronate and alendronate in shaping immunomodulatory profile and angiogenic potential of human periodontal ligament stem cells - Jessica Bria; Emanuela Chiarella; Jessica Sovereto; Francesco Baudi; Marta Greco; Daniela Patrizia Foti; Amerigo Giudice; Anna Di Vito (PLoS ONE, 2025)
Bisphosphonate-related osteonecrosis of the jaw is a significant complication arising from the use of nitrogen-containing bisphosphonates such as Zoledronate (ZOL) and Alendronate (ALN). Although the effects of amino bisphosphonates on bone cells are well established, their influence on human periodontal ligament stem cells (hPDLSCs) remains inadequately explored. This study aimed to evaluate the influence of clinically relevant doses of ZOL and ALN on hPDLSCs secretome composition and its involvement in vascular changes reported in BRONJ. hPDLSCs isolated from the impacted third molar were exposed to increasing concentrations of ZOL (1 μM, 1.5 μM, 2 μM) or ALN (2 μM, 5 μM, 10 μM) for five days. Cytokine assay was directed to measure the levels of IL-1α, IL-6, IL-8, VEGF, and MCP-1. PD-L1 quantification was conducted by immunofluorescence, western blotting and flow cytometry. The angiogenic potential of hPDLSCs-derived secretome after preconditioning with ZOL or ALN was assessed on endothelial cells proliferation, migration, and tube-forming ability. Both ZOL and ALN treatment of hPDLSCs did not result in any significant changes in the secretion of inflammatory markers (IL-1α, IL-6, IL-8, VEGF and MCP-1). ZOL 1.5 μM ( p < 0.0001) and 2 μM ( p < 0.05) induced a down-regulation of total PD-L1. ALN 2 μM and 5 μM promoted a reduction of total ( p < 0.0001) and surface ( p < 0.01) PD-L1, whereas ALN 10 μM induced a rise in surface PD-L1 ( p < 0.0001). Conditioned medium from ZOL- or ALN-treated hPDLSCs impairs cell migration ( p < 0.05) and tube forming ability in vitro ( p < 0.05). In summary, these results suggest that therapeutic concentrations of ZOL and ALN influence the immunomodulatory ability of hPDLSCs by altering PD-L1 expression and reducing the angiogenic potential of hPDLSCs secretome. Both the modulation of inflammation and impairment of angiogenesis may induce unfavorable conditions in periodontal tissue, facilitating the development of osteonecrosis.